Creating teams with an edge the complete skill set to build powerful and influential teams - Luecke, Richard (Boston : Harvard Business School Press, 2004)
Annotation.
Title from title screen.
Includes link to companion web site.
Includes bibliographical references and index.
Keywords: Teams in the workplace; Teams in the workplace; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books